Ecocritical review of the nature essays of university students: a translation and metaphor study - Alican Pandapatan (Erudita: Journal of English Language Teaching, 2023)
The nature of man to understand his ecology is relative linguistically and psychologically. When describing the ecology, a man conveys message using metaphors. This study reviews the essays of students about nature metaphors. The essays were from 75 students. The collected metaphors were translated into English from Filipino. Descriptive method was used. In the study, the majority of the students have the sense of landscape metaphor. The nature is personified as general metaphor. It is like a man who have these senses. There seems to have battle for struggles about exploitation, modification, and destroying. On the other hand, their works also revealed the appreciation of the beauty of nature, its aestheticism. Based on this, theories used in the translation and metaphor study have construed a more sophisticated update on the language studies. Commonalities grouping of metaphors could be different from contexts. It gives more space for analysis and recalibrate the study into wider discussions. Indeed, the use of metaphor in the daily communication helps man to be certain and the gravity of meanings of expressions used. Man is naturally metaphorical which reveal their ability to connect things, concretize abstract forms of meaning, and produce new concepts of semantic terms.